A Rare Case of Localized Esophageal Amyloidosis - Fujiya, Taku (Intern Med, 2020)
A 72-year-old man without any symptoms was referred to our hospital. Esophagogastroduodenoscopy revealed an elevated esophageal lesion that was covered with normal mucosa. The examination of biopsy specimens from the lesion revealed amyloid light-chain (AL) (λ) type amyloid deposits, but there were no amyloid deposits elsewhere in the gastrointestinal tract. Further examinations did not indicate systemic amyloidosis. Thus, this case was diagnosed as a localized esophageal amyloidosis. As the clinical outcome of localized amyloidosis is favorable, this case was scheduled for close follow-up. Localized amyloidosis should be considered in the differential diagnosis of esophageal submucosal tumors.